(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background : Management of critically ill obstetric patients in intensive care unit is a challenge. Pregnancy, delivery and puerperium may be complicated by severe maternal morbidity necessitating Intensive Care Unit (ICU) admission. Management of the critically ill obstetric patient is very complex and requires co-operation of obstetricians with experts of other discipline. Materials and methods : This cross sectional observational study is designed on a total of 50 obstetric patients admitted in ICU, the frequency, socio demographic factor, intervention & outcome. Data was collected by researcher herself and analyzed by appropriate statistical procedure (SPSS- 20) then presented and submitted. Results : Regarding indication of ICU admission eclmpsia was 29(58%) PPH 9(18%) sepsis 5(10%) ruptured uterus 4(8%) and LVF 3(6%) among all patient admitted in ICU 48(98%) got ventilator support during their admission in ICU and 2(4%) were not ventilated. In ICU 23(46%) patients died and 27(54%) were discharged alive. Conclusion : Obstetric patients pose a major management challenge to ICU physicians and obstetricians due to altered physiology during pregnancy, consideration of fetal wellbeing, and the unique type of disorders to be dealt with. As it is a helpful and important facility for the management of obstetric emergency. Establishment of obstetric ICU is essential in all tertiary hospital. JCMCTA 2018 ; 29 (1) : 53-56